2017
DOI: 10.15296/ijwhr.2017.57
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Rupture of Unscarred Uterus at 12 Weeks of Pregnancy: A Case Report and Literature Review

Abstract: IntroductionUterine rupture is an unusual but serious event in pregnancy. Most cases of uterine rupture occur in the second and third trimesters in the scarred uterus (such as previous caesarean section, hysterotomy or myomectomy) (1). The unscarred uterine rupture is an infrequent condition predisposed by multiparity, malpresentation, use of uterotonic drugs (such as oxytocin or prostaglandins), and connective tissue diseases (2). There are some reports regarding uterine rupture in the absence of labor, witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Of this group, most cases had a uterine anomaly (10/23, 43.48%), 3 had a PAS disorder (3/23, 13.04%), 2 had an ART-induced pregnancy (2/23, 8.70%), 2 had a pharmacological termination of pregnancy (2/23, 8.70%), 3 others were multiparous (three or more previous births) (3/23, 13.04%) [9,16,26] (Table 1, Table 2, and Supplementary Tables S3-S5). However, in 4 cases, no clearly recognizable predisposing factor was present (4/19, 21.05%) [8,12,55,77].…”
Section: Variablesmentioning
confidence: 99%
“…Of this group, most cases had a uterine anomaly (10/23, 43.48%), 3 had a PAS disorder (3/23, 13.04%), 2 had an ART-induced pregnancy (2/23, 8.70%), 2 had a pharmacological termination of pregnancy (2/23, 8.70%), 3 others were multiparous (three or more previous births) (3/23, 13.04%) [9,16,26] (Table 1, Table 2, and Supplementary Tables S3-S5). However, in 4 cases, no clearly recognizable predisposing factor was present (4/19, 21.05%) [8,12,55,77].…”
Section: Variablesmentioning
confidence: 99%
“…1,7 In a case series by Vaezi et al, 8 cases of uterine rupture were reported in unscarred uterus at a gestational age below 20 weeks. 8 In all those cases, the fundus was the rupture site. Multiparity was suggested as the main predisposing factor in most cases.…”
Section: Discussionmentioning
confidence: 95%
“…Placenta percreta was observed only in two cases. The defect was repaired in half of the cases [37].…”
Section: Discussionmentioning
confidence: 99%